Fluid flow distribution and pressure drop in split P lattice TPMS structures with varying wall thickness / S.U Zainal ... [et al.] - Zainal, S.U; Manurung, Yupiter HP; Adenan, Mohd Shahriman; Mohamad, Mohd Faizal; Wan Mohamed, Wan Ahmad Najmi (UiTM Press, 2025)
Design for additive manufacturing (DfAM) has enabled the creation of complex lattice structures using selective laser melting (SLM) in additive manufacturing (AM). This study focuses on triply periodic minimal surfaces (TPMS), specifically the split P lattice, which optimizes fluid flow in gas-solid contacting systems for carbon capture applications. The TPMS design enhances gas interaction with large surface areas, crucial for improving mass transfer in chemical processes. Despite significant research on TPMS structures, comprehensive fluid flow analysis for split P lattices in direct air capture (DAC) systems remains limited. This study investigates the effects of varying wall thicknesses (0.4 mm, 0.8 mm, and 1.2 mm) under laminar flow conditions in 5 mm unit cells, across Reynolds numbers (Re) ranging from 25 to 125. Results show that the TPMS structure increases the surface area by 35% and boosts inlet velocity up to fourfold. Thicker walls lead to higher pressure drops and localized acceleration, resulting in a higher velocity profile within smaller pores. The 0.8 mm wall thickness demonstrated the best balance, offering superior area-averaged velocity and uniform flow distribution. Compared to previous TPMS studies, the split P lattice design achieves a more uniform distribution and improved permeability, making it a promising solution for DAC reactor performance.